Shortened fluoroscopy duration and reduced use of contrast dye in cryoballoon-based pulmonary vein isolation procedures using KODEX-EPD's novel occlusion tool. (19th May 2022) - Obergassel, J; Rottner, L; Schleberger, R; Moser, F; Moser, J; Dinshaw, L; Lemoine, MD; My, I; Kirchhof, P; Reissmann, B; Metzner, A; Rillig, A
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Study grant by EPD Solutions, Philips, Netherlands Background: The occlusion tool was recently introduced for KODEX-EPD which is a novel dielectric high-resolution cardiac imaging system. The occlusion tool provides information about level of pulmonary vein occlusion by the cryoballoon (CB) in CB-based pulmonary vein isolation (PVI) ablation procedures for atrial fibrillation (AF). Purpose: Assess effects of the introduction of the occlusion tool on procedural parameters during CB-PVI such as feasibility, acute efficacy and periprocedural safety of KODEX-EPD in different software versions. Methods and Results: 173 consecutive patients (60/173 (35%) paroxysmal AF, 64±12 years, 66/173 (38%) female) underwent CB-PVI with EPD imaging between 08/2019 and 10/2021. 38/173 (22%) of all patients were treated using software version 1.4.6, 33/173 (19%) patients with version 1.4.6a, 41/173 (24%) patients with version 1.4.7 and 61/173 (35%) patients with the latest version 1.4.8. Acute PVI was achieved in all patients. No major periprocedural complications were documented. Software version showed significant effects on procedure duration, fluoroscopy duration and dose area product in ANOVA testing (Figure 1A-C). The largest effect in post-hoc testing was observed for fluoroscopy duration (Figure 1B). Tobit regressions were fitted to model effects of software version on the censored variable contrast volume. All software versions predicted used contrast volume (p<0.00748, Figure 1D). Modelling only effects of procedure date on contrast volume was less accurate than for software version (r²=0.057, p for procedure date = 0.0031) and also a Likelihood-Ratio-Test between different regression models underlined significant effects of software version (p<0.0001). Conclusion: CB-based PVI in combination with its PV-occlusion tool is feasible and safe. The present data strongly suggests a steady positive development of the novel wide-band dielectric imaging and mapping system towards a fluoroscopy- and dye-reduced CB-based AF-ablation. Software versions were introduced sequentially. Therefore time (procedure date) needs to be considered as the most relevant confounder of the described results (e.g. due to a learning curve using the system). However, differentiated statistical testing could show that the results are mainly explained by software version and only much weaker by procedure date.